Soil organomineral fertilization in garlic crop - Oliveira, Roberta Camargos de; Justino Neto, José Francisco; Lana, Regina Maria Quintão; Santos, Ludyellen Cristina Medeiros; Pereira, Alexandre Igor de Azevedo; Luz, José Magno Queiroz (Comunicata Scientiae, 2021)
Garlic (Allium sativum) stands out in the culinary and alternative medicine of many people. The crop is very responsive to adding fertilizers. Commonly the sources used are minerals, but in the last decade the demand for combining these with organic ones has grown, making up the organomineral fertilizers. Due to benefits in the soil and the consequent effect on crops yield, organominerals have been associated as a promising alternative in nutritional management. In this context, the objective was to evaluate the production of garlic under the application of organomineral fertilizer on soil. Quiteria was the variety used in the study. The design was a randomized complete block with five treatments: control (mineral fertilizer in the dose of 100% of the recommendation for the standard crop of the property) and four concentrations of the organomineral fertilizer (100; 80; 60 and 40% of the recommendation for the crop). The percentage of marketable garlic and SPAD index showed no significant difference between the fertilizations evaluated. It was concluded that the use of organomineral fertilizer in the rate of 80% offers the same performance in productivity compared to the 100% mineral, in addition to providing a higher quality in national garlic, as it offers a lower percentage of cull garlic bulbs, adding value in the national garlic chain.